Ammonium metabolism rewiring in the prostate cancer microenvironment: Mechanisms and clinical prospects - Ye, Zihao; Wu, Hao; Li, Zhanhao; Ye, Ruizhe; Rao, Yingliang; Liu, Bin; Gao, Baoshan (Frontiers in Oncology, 2025)
Ammonium metabolism represents a critically understudied yet pivotal driver of prostate tumorigenesis and tumor microenvironment (TME) remodeling. The interplay between tumor metabolic reprogramming and the tumor microenvironment has emerged as a critical frontier in oncology research. While previous studies on prostate cancer metabolism have predominantly focused on lipid metabolism and the Warburg effect, the role of ammonium metabolism, particularly the urea cycle in tumor immune regulation remains insufficiently explored. This metabolic reprogramming constitutes a central node connecting catabolic nutrient breakdown to anabolic biosynthesis by integrating upstream amino acid deamination and transamination reactions with downstream pathways, generating key intermediates including α-ketoglutarate, coenzyme A, and citrate that concurrently fuel the tricarboxylic acid cycle and macromolecular synthesis. Crucially, oncogenic drivers such as Myc and p53 modulate this flux through epigenetic regulation of core enzymes such as glutaminase, glutamine synthetase and ornithine transcarbamylase, thereby channeling metabolism toward tumor progression. The immunomodulatory consequences manifest through dual mechanisms including TME immunosuppression driven by M2 macrophage polarization and immune evasion mediated via glutathione dependent redox homeostasis disruption. Beyond its established role in modulating redox homeostasis, ammonium metabolic reprogramming may additionally trigger novel cell death modalities such as ferroptosis by GSH/GPX4 axis. This emerging pathway offers promising therapeutic avenues for prostate cancer intervention. Synthesizing mechanistically validated insights from in vivo or in vitro models and clinical trials of ammonium-targeting inhibitors, this review proposes novel therapeutic strategies and candidate biomarkers. Moreover, the unique citrate and polyamine metabolism characteristics of prostate cancer may be impacted by these processes, offering promising avenues for future treatments.